Dignity and the organization - Kostera, Monika, 1963-; Pirson, Michael (Palgrave Macmillan, 2017)
This important book focuses on the role of human dignity, its protection and promotion in the context of organization and Humanistic Management. The recent phenomenon of humanism in management already has a rich body of literature and takes up many themes both theoretically, and from a practitioner perspective. Dignity and the Organization is the first book to explicitly deal with the topic of human dignity and management. The chapters address various aspects and problems from a humanistically-oriented perspective, taking up issues relevant for the contemporary management theorists and practitioners, and are concerned with organization, management and the social and cultural context. The book develops the notion of human dignity in conceptual and theoretical terms in its practical application, within the context of organizations.- Resumé vydavatel
Keywords: organizační chování; personální management; lidská důstojnost; organizational behavior; personnel management; human dignity; elektronické knihy; sborníky; electronic books; papers of several authors